Improving the adoption of thyroid cancer clinical practice guidelines. (14th April 2016) - Likhterov, Ilya; Tuttle, R. Michael; Haser, Grace C.; Su, Henry K.; Bergman, Donald; Alon, Eran E.; Bernet, Victor; Brett, Elise; Cobin, Rhoda; Dewey, Eliza H.; Doherty, Gerard; Dos Reis, Laura L.; et al.
Abstract : Objectives/Hypothesis: To present an overview of the barriers to the implementation of clinical practice guidelines (CPGs) in thyroid cancer management and to introduce a computer‐based clinical support system. Data Sources: PubMed. Review Methods: A review of studies on adherence to CPGs was conducted. Results: Awareness and adoption of CPGs is low in thyroid cancer management. Barriers to implementation include unfamiliarity with the CPGs and financial concerns. Effective interventions to improve adherence are possible, especially when they are readily accessible at the point of care delivery. Computerized clinical support systems show particular promise. The authors introduce the clinical decision making modules (CDMMs) of the Thyroid Cancer Care Collaborative, a thyroid cancer‐specific electronic health record. These computer‐based modules can assist clinicians with implementation of these recommendations in clinical practice. Conclusion: Computer‐based support systems can help clinicians understand and adopt the thyroid cancer CPGs. By integrating patient characteristics and guidelines at the point of care delivery, the CDMMs can improve adherence to the guidelines and help clinicians provide high‐quality, evidence‐based, and individualized patient care in the management of differentiated thyroid cancer. Laryngoscope, 126:2640–2645, 2016